(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To survey dengue fever mosquito indices and describe the knowledge, attitudes, and disease prevention practices of residents in Ward 3, District 8, Ho Chi Minh City. Research methods: A cross-sectional descriptive study was conducted in Ward 3, District 8, Ho Chi Minh City from June 2024 to November 2024 on 550 residents aged 15 and over living in the area, using Ae. aegypti and Ae. albopictus mosquitoes; data were collected through direct interviews using a structured questionnaire combined with vector investigation. Results: The study showed that 100% of the collected mosquitoes were Aedes aegypti, with females accounting for 62.7%. Mosquito and larval indices were low (DIₐₑ = 0.12 mosquitoes/house; CI = 3.13%; BI = 5.6; larval density/house = 0.07). Mosquitoes mainly rested indoors, with larval breeding grounds commonly found in potted plants and flower vases. Results showed that 44.7% of residents had correct general knowledge; 33.8% had correct general attitudes; and 53.6% fully implemented dengue fever prevention measures. Conclusion: Mosquito and Aedes aegypti larval indices in Ward 3, District 8 were low. However, the rate of correct knowledge, attitudes, and practices among residents remains limited, indicating the need for continued strengthening of communication and dengue fever prevention practices.